Characteristics of high-performance BaHfO3-doped SmBa2Cu3Oy superconducting films fabricated with a seed layer and low-temperature growth. (30th April 2015) - Miura, S; Yoshida, Y; Ichino, Y; Matsumoto, K; Ichinose, A; Awaji, S
Abstract: BaHfO3 (BHO)-doped SmBa2 Cu3 O y (SmBCO) superconducting films were fabricated with a seed layer and low-temperature growth (LTG technique) via pulsed laser deposition. The LTG technique enables the fabrication of high-quality SmBCO films even at a low substrate temperature during the deposition, and also greatly increases the number density of BHO nano-rods. Transmission electron microscopy observations showed that the 5.6 vol% BHO-doped sample had a high number density [(4.8 ± 0.3) × 10 3 μ m −2 ] of small (5.4 ± 0.7 nm) BHO nano-rods. This sample exhibits maximum flux pinning forces ( F p ) of 405 GN m −3 in 9.0 T at 40 K and 105 GN m −3 in 9.0 T at 65 K. The high density and small size of the nano-rods in a REBa2 Cu3 O y matrix (where RE is a rare earth element) is considered to be very effective for enhancing F p at low temperatures under a high field.